An outlook on procedures of conjugating folate to (co)polymers and drugs for effective cancer targeting. Issue 7 (8th June 2020) - Kharkar, Prashant S.; Soni, Govind; Rathod, Vaibhavi; Shetty, Saritha; Gupta, M. K.; Yadav, Khushwant S.
Abstract: Folate receptors (FRs) are expressed in vast majority of cancers. Selective targeting of the FRs is, therefore, one of the most popular and sought‐after strategies for improving the efficacy of cancer therapeutics. Variety of approaches involving folate conjugation to several well‐known and novel, nontoxic, biodegradable, and biocompatible (co)polymers have been attempted and successfully applied to a large number of nanoparticulate drug delivery systems (micelles, liposomes, nanoparticles, quantum dots, mesoporous silica‐based materials, and others) in the last decade‐and‐a‐half. Standard and novel synthetic approaches were utilized for the conjugation, followed by the formulation of the drug delivery modality. In most of the cases, the targeted system lived up to its reputation, validating its usefulness in targeted cancer therapeutics. The present review summarizes the progress and state‐of‐the‐art synthetic methodologies for folate conjugation to (co)polymers, drugs, and nucleic acids. The limitations of the FR targeting are discussed in brief to give the reader the other side of the story. Finally, the information on marketed folic acid conjugates highlight their industrial applications.